2011
DOI: 10.1002/ejoc.201100913
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biaryls by Pd‐Catalyzed Decarboxylative Homo‐ and Heterocoupling of Substituted Benzoic Acids

Abstract: By carefully choosing the right substrate ratio, catalyst combination, and base, symmetrical and unsymmetrical biaryls can be readily synthesized through the Pd‐catalyzed decarboxylative homo‐ and heterocoupling of substituted benzoic acids. The reaction gave the desired products in 40–90 % yield and is compatible with 2‐nitro‐, 2‐methoxy‐, 2‐fluoro‐, and 2‐chloro‐substituted benzoic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…In 2011, Tan, Deng, and coworkers [27] showed that not only symmetrical but also unsymmetrical biaryls can be efficiently synthesized through the Pd-catalyzed decarboxylative homocoupling or heterocoupling of substituted benzoic acids. During the preparation of their manuscript, Larrosa and coworkers [28] reported a Pd-catalyzed decarboxylative homocoupling of arenocarboxylic acids to afford symmetrical biaryls (Scheme 3.14).…”
Section: Scheme 37mentioning
confidence: 99%
“…In 2011, Tan, Deng, and coworkers [27] showed that not only symmetrical but also unsymmetrical biaryls can be efficiently synthesized through the Pd-catalyzed decarboxylative homocoupling or heterocoupling of substituted benzoic acids. During the preparation of their manuscript, Larrosa and coworkers [28] reported a Pd-catalyzed decarboxylative homocoupling of arenocarboxylic acids to afford symmetrical biaryls (Scheme 3.14).…”
Section: Scheme 37mentioning
confidence: 99%
“…Their disadvantage, relative to decarboxylative methods, is the production of stoichiometric amounts of salt by‐products that can sometimes be challenging to separate from the desired products. Decarboxylative couplings have demonstrated their versatility when applied to homo‐coupling reactions of ortho ‐substituted benzoic acids or 2‐substituted heteroaromatic carboxylic acids 19,20. These coupling reactions typically require a copper or silver co‐catalyst to facilitate the decarboxylation step.…”
Section: Introductionmentioning
confidence: 99%
“…[13] The addition of the phosphine ligand PCy 3 (15 mol %) to the reaction system resulted in an increase of the yield of product 3 a to 30 % (entry 3), thus illustrating the beneficial effect of the phosphine ligand. While varying the phosphine it was found that in the cases in which a poor yield of 3 a was obtained, the yields of side-products arising from protodecarboxylation and/or homocoupling increased significantly (entries [10][11][12][14][15][16][17]; it was further noted that whereas electron-deficient aryl carboxylic acid 2 a underwent both homocoupling and protodecarboxylation side reactions, the electron-rich substrate 1 a underwent predominant protodecarboxylation. Additionally, it was observed that varying the ratio of DMSO to dioxane also had an effect on the yield of 3 a (entries [4][5][6].…”
mentioning
confidence: 99%
“…Notably, the biaryl products arising from the decarboxylative cross-coupling reaction of electron-deficient aryl carboxylic acids were isolated in good yield (4 a-4 h); these products are not readily accessible using conventional crosscoupling methods because the required organometallic reagents are difficult to synthesize or are of low reactivity. [14] Experimental Section [12b] The variety of aryl substituents tolerated in these cross-coupling reactions, such as fluoro, chloro, bromo, trifluoromethyl, methoxyl, cyano, and nitro, provide opportunities for further synthetic elaboration.…”
mentioning
confidence: 99%
See 1 more Smart Citation